2023
DOI: 10.1039/d2rp00160h
|View full text |Cite
|
Sign up to set email alerts
|

Secondary chemistry teacher learning: precursors for and mechanisms of pedagogical conceptual change

Abstract: Despite years of research and practice inspired by chemistry education research, a recent report shows that US secondary instruction is not aligned with current national reform-based efforts. One means to mitigate this discrepancy is focusing on pedagogical conceptual change, its precursors (higher self-efficacy and pedagogical discontentment), and the subtleties of its mechanisms (assimilation and accommodation). In this study, we investigate the final reflections of participants (N = 35) who completed our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 84 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Figure 4 shows the frequencies of CF codes and their prevalence among VCI-2 teachers. Regarding the nature of teacher−teacher feedback, the greatest number was Praise (93) with the fewest being Critique (7). Describe (57), Elaborate (47), and Suggest (41) were also more frequent than other CF codes such as Recollect (14) and Take Up (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 shows the frequencies of CF codes and their prevalence among VCI-2 teachers. Regarding the nature of teacher−teacher feedback, the greatest number was Praise (93) with the fewest being Critique (7). Describe (57), Elaborate (47), and Suggest (41) were also more frequent than other CF codes such as Recollect (14) and Take Up (10).…”
Section: Discussionmentioning
confidence: 99%
“…Feedback should assist teachers in expanding their views so the epistemological differences between traditional and reform-based teaching can be more easily discerned. 54 Teacher−teacher feedback should therefore instigate a sense of pedagogical discontentment, 55 giving rise to pedagogical conceptual change 7 and even a reshaping of one's core teaching identity. 56 Thompson and Zeuli 57 furthermore described coinciding requirements for teachers' transformative rethinking.…”
Section: ■ Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to note that accommodation is operationalised for this study in MoP and in a manner dissimilar to the role of accommodation found within the conceptual change model (Strike and Posner, 1992) or in pedagogical conceptual change (Wu and Yezierski, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Specific, accessible, and practical redox teaching moves that uses the limitations of the symbolic level for warranting sensemaking with the particulate also require further investigation (Wu and Yezierski, 2022b). By problematizing current epistemologies associated with redox, we can begin generating the necessary precursors for pedagogical conceptual change towards reform-based instructional practices (Wu and Yezierski, 2023).…”
Section: For Researchersmentioning
confidence: 99%